Loss of lamin B1 results in prolongation of S phase and decondensation of chromosome territories - Camps, Jordi (Federation of American Societies for Experimental Biology, 2014)
Nuclear lamin B1 (LMNB1) constitutes one of the major structural proteins in the lamina mesh. We silenced the expression of LMNB1 by RNA interference in the colon cancer cell line DLD-1 and showed a dramatic redistribution of H3K27me3 from the periphery to a more homogeneous nuclear dispersion. In addition, we observed telomere attrition and an increased frequency of micronuclei and nuclear blebs. By 3D-FISH analyses, we demonstrated that the volume and surface of chromosome territories were significantly larger in LMNB1-depleted cells, suggesting that LMNB1 is required to maintain chromatin condensation in interphase nuclei. These changes led to a prolonged S phase due to activation of Chk1. Finally, silencing of LMNB1 resulted in extensive changes in alternative splicing of multiple genes and in a higher number of enlarged nuclear speckles. Taken together, our results suggest a mechanistic role of the nuclear lamina in the organization of chromosome territories, maintenance of genome integrity and proper gene splicing.—Camps, J., Wangsa, D., Falke, M., Brown, M., Case, C. M., Erdos, M. R., Ried, T. Loss of lamin B1 results in prolongation of S phase and decondensation of chromosome territories.